Ligament-Derived Stem Cells: Identification, Characterisation, and Therapeutic Application - Katie Joanna Lee; Peter David Clegg; Eithne Josephine Comerford; Elizabeth Gail Canty-Laird (Stem Cells International)
Ligament is prone to injury and degeneration and has poor healing potential and, with currently ineffective treatment strategies, stem cell therapies may provide an exciting new treatment option. Ligament-derived stem cell (LDSC) populations have been isolated from a number of different ligament types with the majority of studies focussing on periodontal ligament. To date, only a few studies have investigated LDSC populations in other types of ligament, for example, intra-articular ligaments; however, this now appears to be a developing field. This literature review aims to summarise the current information on nondental LDSCs including in vitro characteristics of LDSCs and their therapeutic potential. The stem cell niche has been shown to be vital for stem cell survival and function in a number of different physiological systems; therefore, the LDSC niche may have an impact on LDSC phenotype. The role of the LDSC niche on LDSC viability and function will be discussed as well as the therapeutic potential of LDSC niche modulation.